Human parvovirus B19 infections among exanthematic diseases notified as measles - Rita C.N. Cubel; Marilda M. Siqueira; Elisabete O. Santos; Maria F. Pires; Célia M. F. Cruz; Jussara P. Nascimento (Revista da Sociedade Brasileira de Medicina Tropical, 1997)
A total of 1397 sera collected from 1095 cases of exanthematic disease notified as measles in ES and RJ states during July 1992 to December 1994 were investigated. These sera were first tested for measles and rubella specific IgM. When they proved negative, they were tested for B19 specific IgM by an enzyme immunoassay. B19 infection was confirmed in 27 (2.5%) of these cases. Sera from 194 negative cases for measles and rubella IgM received from other Brazilian states were also investigated and B19 infection was confirmed for 11 of them. Sera from these 38 IgM positive cases for B19, were tested for anti-B19 IgG by an enzyme immunoassay and for B19 DNA by dot blot hybridization. Anti-B19 IgG antibodies were detected in most of the acute sera. B19 DNA was detected in the acute serum of one patient that had been splenectomized before. As the exanthem caused by human parvovirus infection may be clinically diagnosed as rubella, it could be important to diagnose B19 infection in Brazil since it is becoming prevalent as the cause of rash in countries where rubella is controlled by vaccination. Um total de 1397 soros colhidos de 1095 casos de exantema notificados como sarampo, nos estados do ES e RJ, no período de julho de 1992 a dezembro de 1994, foram investigados. Estes soros foram inicialmente testados para sarampo e rubéola por detecção de IgM específica. Os casos negativos foram então testados para a presença de IgM específca anti-B19 por um ensaio imunoenzimático. A infecção pelo B19 foi confirmada em 27 (2,5%) destes casos. Soros de 194 casos negativos para sarampo e rubéola provenientes de outros estados brasileiros foram também investigados, e a infecção pelo B19 pode ser confirmada em 11 destes casos. Os soros dos 38 casos IgM positivos para B19 foram testados para a presença de IgG específica anti-B19 por um ensaio imunoenzimático, e para a presença do ADN viral por hibridização em "dots" (dot blot). IgG específica anti-B19 pode ser detectada na maioria dos soros de fase aguda, e o ADN viral foi detectado ...